Processing speed of morphological understanding of verbs in preschool children with specific language disorders and its relationship with the inhibitory control - Urrutia Martínez, Mabel; Roa Inostroza, Miriam Alejandra (Revista de Investigación en Logopedia, 2020)
In recent times the relationship of Specific Language Disorder with some cognitive functions such as memory, attention and executive functioning has been studied, but few studies in Spanish have investigated the relationship of psychological and linguistic variables as a whole The objective of this study was to observe the relationship between cognitive and linguistic aspects, addressing the grammatical problems of Specific Language Disorder, specifically the morphological comprehension of verbs and the reaction time in the processing of such tasks. The participants were monolingual Spanish-speaking boys and girls with a diagnosis of SLI in the preschool period and a control group. Through an experimental design, the response time and the number of hits go / no go in the processing of verbal morphological aspects were measured. Such measures were related to the use other variables such us behavioral inhibition in a non-verbal task, speed of naming at the level of linguistic production and visual working memory from a neuropsychological evaluation. The results showed that children with SLI spent more time in identifying irregular verbs compared to regular verbs and a longer time in the identification of verbs in simple past tense compared to the control group. In terms of inhibitory control, children with SLI had a higher rate of errors in tasks of inhibition compared to the control group and a higher rate of errors in the comprehension of both types of verbs and both verbal tenses.
Keywords: executive funtions; inhibitory control; processing speed; specific language disorders